2015
DOI: 10.1002/ejp.636
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of pain extent and pain location using a novel method for pain drawing analysis

Abstract: A novel method for the acquisition of PD was presented. Test-retest reliability of reporting pain extent and pain location was supported in people with CNP and CLBP. Future research is needed to establish psychometric properties of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(158 citation statements)
references
References 28 publications
8
144
2
Order By: Relevance
“…In fact, the results support that women may actually underestimate the extent of their pain distribution on masculine body charts. However, this may also be an indication of that widespread or multisite pain is more difficult to reproduce on 2 consecutive pain drawings than focal pain [14]. Whether this could increase the likelihood that women’s pain drawings are labelled as ‘nonorganic’, a condition that has been suggested to stem from a psychosocial disturbance, given that the criterion for this condition is a wide distribution of pain over many anatomic regions [25], is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the results support that women may actually underestimate the extent of their pain distribution on masculine body charts. However, this may also be an indication of that widespread or multisite pain is more difficult to reproduce on 2 consecutive pain drawings than focal pain [14]. Whether this could increase the likelihood that women’s pain drawings are labelled as ‘nonorganic’, a condition that has been suggested to stem from a psychosocial disturbance, given that the criterion for this condition is a wide distribution of pain over many anatomic regions [25], is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Is this difference in pain area between the genders a true depiction and is there any clinical relevance between the differences? Few studies, have employed gender-specific or more feminine body charts [14-16]; however, no studies have cross-validated a female to a male body chart nor investigated whether the patient prefers using gender-specific body charts for expressing and communicating their pain. Indeed, it has been proposed that men and women experience and communicate pain differently [17], the question is whether a female body chart provides the otherwise missing and necessary anatomical guidance required for women to more clearly and accurately express their pain; and if so, does the use of high-resolution, three-dimensional (3D) body charts further improve this form of communication?…”
Section: Introductionmentioning
confidence: 99%
“…Some methods to score PDs have been developed, aiming to quantify the pain area. These methods include the grid system (Margolis method), the classification into “organic” or “non‐organic” (Udén method), Ransford penalty points, Sivik penalty points, and, more recently, computerized assessment …”
Section: Introductionmentioning
confidence: 99%
“…The development of computerized methods has facilitated the more precise measurement of pain extent and has made interpretation more standardized. Barbero et al . developed a method in which clinicians collect information about the pain area using a tablet and a predefined image of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Neubert et al using PDs from different chronic pain populations, found ICCs from 0.92 to 0.97 for pain extent [11,21]. Which drawing is "correct"?…”
Section: Comparison Of Patients' and Doctors' Drawingsmentioning
confidence: 99%